The Effect of Using Electronic Visual Notation on Developing Visual ‎Thinking Skills among Deaf Female Students in High School - Aljabr, Eman Abdulaziz Mohammed (Dirasat: Educational Sciences, 2025)
Objectives: The study aims to investigate the impact of using electronic visual note-taking on developing visual thinking skills among deaf female students at the secondary level in Riyadh. Methods: To achieve the study’s objectives, the researcher designed a learning environment based on electronic visual note-taking and developed a scale for visual thinking skills, which included three skills: (1) information analysis, (2) information interpretation, and (3) meaning inference. This scale was applied to a sample of six deaf female students. The study followed a quasi-experimental approach using a one-group pre-test/post-test design. Results: The study results revealed statistically significant differences at the significance level (α = 0.05) between the mean scores of the experimental group in the pre-test and post-test on the dimensions of visual thinking skills, in favor of the post-test. Conclusions: The findings highlighted the positive impact of using electronic visual note-taking in developing visual thinking skills among deaf female secondary students. Accordingly, the study recommended the importance of holding training courses for teachers of deaf female students to learn how to use electronic visual note-taking and to incorporate it as a method of teaching in secondary education for deaf students.